Subclinical Left Ventricular Dysfunction is Influenced by Genotype Severity in Patients with Cystic Fibrosis. Issue 12 (August 2018) - Pallin, Michael; Keating, Dominic; Kaye, David M; Kotsimbos, Tom; Wilson, John W
Background and objective: Over 2000 genotypes in the cystic fibrosis (CF) gene have been described. These genotypic differences result in variable clinical manifestations of CF, with severity of disease dependent on CF transmembrane conductance (CFTR) protein function. CFTR is widely distributed in nucleated cells, including cardiac myocytes, but the effect of genotype on cardiac function is not known. Methods: This retrospective review of echocardiographic data is from a single adult CF centre between 2000 and 2015. Patients were cohorted based on the functional classification of genotype. 'Severe' patients had both CF genes from functional classification groups 1-3; 'mild' patients had one or no gene from these groups, or in the event of the second gene being unknown were pancreatic sufficient. Results: Genotype and echocardiography were recorded during the inclusion period in 100 patients, 79 of whom were classified as having severe genotypes. Although the severe group were younger they had a lower fractional shortening (33.66 ± 6.6 vs 36.9 ± 6.3, P < .05), left atrial area (14.9 ± 3.6 versus 18.0 ± 4.2 cm 2 ; P < .01) and volume (39.9 ± 18.7 versus 51.0 ± 18.7 mL; P < .05) and showed a trend to lower left ventricular ejection fraction. Conclusions: This study is the first to show that in CF, severity of genotype (functional classification) is associated with cardiac impairment. Patients with severe CF genotype and cardiac dysfunction should be identified to evaluate cardiac response to gene-modifying treatments prior to consideration for lung transplantation.